2020
DOI: 10.1016/j.breast.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of breast cancer with special histological types: A surveillance, epidemiology, and end results database analysis

Abstract: Objectives To explore the clinicopathological features and prognosis of breast cancer with special histological types. Materials and methods The information of breast cancer patients was obtained from the Surveillance, Epidemiology, and End Results (SEER) database (2010–2016). Comparative analyses were performed to explore the difference in clinicopathological characteristics and propensity score matching (PSM) was used to weaken the effects from clinical profiles. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
(26 reference statements)
4
24
0
Order By: Relevance
“…Risk factors for SCC were identified, including older age, advanced disease TNM stage, and organ involvement, which were similar to the data reported by prior studies focusing on breast cancer with other histologic types. 14,15 Our study highlighted the substantial heterogeneity in the clinical features of breast cancer with squamous differentiation. Currently, clinical trials designed for breast cancer tend to ignore the histological classifications, which probably results in bias regarding clinical significance.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Risk factors for SCC were identified, including older age, advanced disease TNM stage, and organ involvement, which were similar to the data reported by prior studies focusing on breast cancer with other histologic types. 14,15 Our study highlighted the substantial heterogeneity in the clinical features of breast cancer with squamous differentiation. Currently, clinical trials designed for breast cancer tend to ignore the histological classifications, which probably results in bias regarding clinical significance.…”
Section: Discussionmentioning
confidence: 76%
“…Risk factors for SCC were identified, including older age, advanced disease TNM stage, and organ involvement, which were similar to the data reported by prior studies focusing on breast cancer with other histologic types. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…This finding are consistent with NCCN (National Comprehensive Cancer Network 2020 guideline) where it mention that MBC are highly unusual to have ER positive biology. Triple negative subtype of MBC revealed inferior outcome and poorer prognosis when compared to their invasive ductal carcinoma counterparts [ 1 ]. This brings about limited potential of targeted therapies for patients diagnosed with MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Metaplastic breast carcinoma (MBC) is a rare type of breast carcinoma and is well recognised for its heterogeneity and worse prognosis compared to the other types of breast carcinoma [ [1] , [2] , [3] ]. Previous studies reported incidence of MBC of less than 1% of all types of breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no statistically significant difference existed in OS between ACC and MC, which was favorable histology and generally ER positive and Her2 negative [ 12 , 13 ]. Given its rarity and good prognosis, the value of adjuvant therapy in patients with ACC of the breast remained controversial and led to large variations in clinical practice [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%